Some Regional Aspects of the Building Boom, 1924-36 - Bowley, Marian (Review of Economic Studies, 1938)
Journal Article Some Regional Aspects of the Building Boom, 1924–36 Get access Marian Bowley Marian Bowley Dundee Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 5, Issue 3, June 1938, Pages 172–186, https://doi.org/10.2307/2967445 Published: 01 June 1938